Affect of Covid-19 on The Construction Industry and Tackling the Impacts of Covid-19 on the Construction Project - Syed Abdul Kareem Shajahan (International Journal of Scientific Research in Civil Engineering, 2022)
COVID-19 pandemic has become a worldwide health concern that is impacting every aspect of everyone’s life. The COVID-19 pandemic is having a significant impact on the economically sensitive construction industry. On the positive side, however, the construction sector has a lot of potentials to boost the recovery thanks to its job creation potential; and in return, remedial measures can support the transformation of the sector towards sustainability and digitization. Tripartite cooperation and social dialogue, along with international labour standards, are key to promoting a people-centred recovery in the construction sector from the crisis. This article explores the measures that construction businesses measure put in place to mitigate the risks of a legal proceeding related to potential contract terms due to COVID-19. Further, this study provides a chance about the measures adopted by construction companies in avoiding written agreement disputes precipitated by the Covid-19 pandemic. In addition to that, it can aid the businesses in minimizing risks and scaling back defrayment and uncertainties so as to focus attention on maintaining existing written agreement relationships to secure future businesses. The suggestions made could be used by construction businesses to enhance the strategy used to stop COVID-19 from spreading on-site. This article could also provide policymakers with information on COVID-19 measures that are not being properly implemented on the ground and need further scrutiny. Research on health and safety precautions for building sites during this COVID-19 season is still being developed. Consequently, this work advances the body of knowledge in this field of study.
Keywords: COVID-19; Pandemics; Construction Industry; Impact